Clockwork princess - Clare, Cassandra (New York : Margaret K. McEldeberry Books, 2013)
When seventeen-year-old orphaned shapechanger Tessa Gray is kidnapped by the villainous Mortmain in his final bid for power, the London Institute rallies to save her, but is beset by danger and betrayal at every turn.
Keywords: Paranormal fiction; Demonology -- Juvenile fiction; Orphans -- Juvenile fiction; Secret societies -- Juvenile fiction; London (England) -- History -- 19th century -- Juvenile fiction; Great Britain -- History -- Victoria, 1837-1901 -- Juvenile fiction; Fantasy fiction